Green facilities handbook : simple & profitable strategies for managers - Woodroof, Eric A. (Fairmont Press ; CRC Press, 2009)
Meeting a need in the marketplace for information on how to operate a sustainable facility and reduce carbon emissions, the Green Facilities Handbook clearly explains why green business is good business and delineates practical strategies to green your operations in energy and management. The book explores issues in the greening of a facility, including janitorial considerations, fuel choices for fleets, and recycling. Additional information is provided on carbon reduction terminology, monitoring and reporting, and carbon trading as well as offset strategies. Special bonus chapters include valuable information on financing and procedures for green marketing.
Keywords: Sustainable buildings -- Handbooks, manuals, etc.; Facility management -- Handbooks, manuals, etc.; Commercial buildings -- Energy conservation -- Handbooks, manuals, etc.; elektronické knihy; electronic books